Compliance behavior of farmers towards the payment of paddy zakat: case study in Kuala Muda, Kedah / Nor Diyana Rosli and Sumayyah Noraslam - Rosli, Nor Diyana; Noraslam, Sumayyah (2012)
The issue on compliance behavior of zakat payment on income and business has been discussed frequently by both academicians and practitioners, however there is little research specifically on paddy zakat. In fact, collection of paddy zakat at department of Zakat of Kuala Muda from 2009 to 2011, also indicate the decrease trend of collection of paddy zakat. Therefore, the purpose of this research is to examine relationship between the levels of religiosity, level of knowledge and organization’s factor towards compliance behavior and to identify the most influence factor towards compliance behavior. The target population is paddy farmers whose are fulfilling the criteria to pay paddy zakat in District of Kuala Muda, the largest area of paddy field in Kedah. In order to examine the relationship between the variables, this study will utilize Descriptive Analysis and Pearson Correlation meanwhile, the Multiple Regression analysis will be used to quantify the significant factor.